Konversi Agama dalam Perpsektif Islam - Hermawan, Rudi; Rohimah, Siti (TSAQOFAH, 2026)
Religious conversion is a complex and multidimensional socio-religious phenomenon because it involves changes in belief, religious identity, and value orientation in an individual’s life, which, in a plural society, is understood not only as a theological issue but is also closely related to psychological, social, cultural, and spiritual aspects. This study aimed to describe the definition and meaning of religious conversion, examine the processes experienced by individuals in undergoing religious conversion, identify the factors that influence it, and analyze Islamic perspectives on this phenomenon. The method used was a literature review by examining various scholarly works, expert opinions, and normative Islamic sources in the form of the Qur’an and hadiths. The findings show that religious conversion generally unfolds through stages of awareness, meaning-seeking, and decision-making, which are influenced by individuals’ psychological conditions, social environment, culture, and spiritual experiences. From an Islamic perspective, religious conversion is viewed as a fundamental matter of aqidah, in which freedom of religion is acknowledged, but faith and steadfastness in Islam are strongly emphasized. Therefore, the phenomenon of religious conversion needs to be understood comprehensively and proportionally so as not to generate social conflict and to ensure that religious and humanitarian values are respected.